2005
DOI: 10.1098/rspb.2005.3363
|View full text |Cite
|
Sign up to set email alerts
|

Cascading host-associated genetic differentiation in parasitoids of phytophagous insects

Abstract: The extraordinary diversity of phytophagous insects may be attributable to their narrow specialization as parasites of plants, with selective tradeoffs associated with alternate host plants driving genetic divergence of host-associated forms via ecological speciation. Most phytophagous insects in turn are attacked by parasitoid insects, which are similarly specialized and may also undergo host-associated differentiation (HAD). A particularly interesting possibility is that HAD by phytophagous insects might lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
170
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(184 citation statements)
references
References 57 publications
7
170
4
1
Order By: Relevance
“…However, the limited number of studies investigating cascading HAD of parasitoids, have produced mixed results even within closely related systems. For instance, Stireman et al (2006) found that parasitoids of 2 goldenrod gall makers, which have diverged genetically along host plant lines, also exhibit cascading HAD. However the eurytomid, Eurytoma gigantea Walsh, which attacks the stem galling tephritid fly, Eurosta solidaginis Fitch, another galler of the same 2 goldenrod species has not diverged in parallel with its phytophagous host (Cronin & Abrahamson 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the limited number of studies investigating cascading HAD of parasitoids, have produced mixed results even within closely related systems. For instance, Stireman et al (2006) found that parasitoids of 2 goldenrod gall makers, which have diverged genetically along host plant lines, also exhibit cascading HAD. However the eurytomid, Eurytoma gigantea Walsh, which attacks the stem galling tephritid fly, Eurosta solidaginis Fitch, another galler of the same 2 goldenrod species has not diverged in parallel with its phytophagous host (Cronin & Abrahamson 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the gall midge, probably through ovipositional mistakes, established populations on the 2 derived host plants (I. frutescens and I. imbricata) and midges from these 2 plants are significantly smaller (owing to increased larval crowding in their smaller galls) compared to midges that develop on B. frutescens. Asphondylia borrichiae exhibit consistent size and genetic differences that Stireman et al (2006) refer to as host-associated differentiation (HAD) at the level of the plant genus. The apparent trade-off for decreased size and fecundity of A. borrichiae populations that utilize the 2 Iva spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, random association in natural communities cannot be assumed, as demonstrated by the preference or host-associated differences (HAD) for a number of phytophagous insects to different goldenrod genotypes (Stireman et al 2005). Furthermore, the recent discovery that insect-host genetic differences promote parasitoid cryptic diversity, through cascading HAD, suggests that the evolutionary trajectory of the parasitoid will be influenced by genotypic interactions between interacting species (Stireman et al 2006). …”
Section: June 2010 1567 Genotypic Interactions Influence Ieesmentioning
confidence: 99%
“…Megastigmus dorsalis sp.2 also contains two divergent genetic lineages that attack galls on different host‐plant taxa, with one host race attacking galls on section Cerris oaks and the other attacking galls on section Quercus oaks. These results show that some of the same host traits structure both intraspecific genetic diversity and multispecies composition in the oak gall parasitoid community (Bailey et al., 2009), highlighting the importance of tri‐trophic niches in promoting cascades of diversification across interacting trophic levels (Feder & Forbes, 2010; Forbes et al., 2009; Hood et al., 2015; Nyman, Bokma, & Kopelke, 2007; Stireman et al., 2006). Our results also underline the need for more data, even in systems such as the oak gall wasp community that are relatively well known, in order for the subtleties of HAD to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…High herbivore host diversity and shared generalist natural enemies can be reconciled if apparent generalist enemies in fact comprise genetically divergent cryptic lineages that each attack only a subset of the species’ recorded host range. Such structuring has been revealed in a range of systems (Forbes, Powell, Stelinski, Smith, & Feder, 2009; Hood et al., 2015; Smith, Wood, Janzen, Hallwachs, & Hebert, 2007; Smith et al., 2008; Stireman et al., 2006). More broadly, understanding how insect herbivores and parasitoid communities are structured has implications for many aspects of ecosystem management, including biological control of herbivorous pests (Carvalheiro, Buckley, Ventim, Fowler, & Memmott, 2008; Henneman & Memmott, 2001), and predicting the impacts of range expansions associated with anthropogenic introductions and climate change (Nicholls, Fuentes‐Utrilla, et al., 2010; Sax et al., 2007).…”
Section: Introductionmentioning
confidence: 99%